Implementasi Teori Belajar Behavioristik Terhadap UMKM “Bintang Lestari” Dalam Pemasaran Melalui Media Sosial - Gusti Putu Devandra Yudhistira; Ugy Soebiantoro (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Repetition and practice are used in Behavioristic learning methods. Group 32 Students of the East Java "Veteran" National Development University in 2023 use this theory to apply marketing knowledge through social media towards "Bintang Lestari" MSME. The ability to introduce businesses and upload products on social media is something that can help MSME achieve good business performance. Prior to receiving assistance, The"Bintang Lestari" MSME only marketed their products conventionally by word of mouth. After mentoring "Bintang Lestari" managed to use Whatsapp Business and Facebook and get orders from these applications.